High Circulating Chemokines (C-X-C Motif) Ligand 9, and (C-X-C Motif) Ligand 11, in Hepatitis C-Associated Cryoglobulinemia. (January 2013) - Antonelli, A.; Fallahi, P.; Ferrari, S.M.; Frascerra, S.; Mancusi, C.; Colaci, M.; Manfredi, A.; Sansonno, D.; Zignego, A.L.; Ferri, C.
(C-X-C motif) ligand 9 and (C-X-C motif) ligand 11 (CXCL9 and CXCL11), are potent chemoattractants for activated T cells, and play an important role in T helper 1 (Th) 1 cell recruitment in chronic hepatitis C. No study has evaluated CXCL9, together with CXCL11, circulating levels in patients with mixed cryoglobulinemia and hepatitis C (MC+HCV-p). The aim of the present study therefore was to measure serum CXCL9, and CXCL11 levels, in MC+HCV-p, and to relate the findings to the clinical phenotype. Serum CXCL9 and CXCL11 were measured in 71 MC+HCV-p and in matched controls. MC+HCV-p showed significantly higher mean CXCL9 and CXCL11 levels than controls (P < 0.001, for both), in particular, in 32 patients with active vasculitis (P < 0.001). By defining high CXCL9 or CXCL11 level as a value of at least 2 SD above the mean value of the control group (> 100 pg/mL): 89% MC+HCV-p and 5% controls had high CXCL9 (P < 0.0001, chi -square); 90% MC+HCV-p and 6% controls had high CXCL11 (P < 0.0001, chi -square). In a multiple linear regression model of CXCL9 vs age, ALT, CXCL11, only CXCL11 was significantly (r = 0.452, P < 0.0001) and independently related to CXCL9. Our study demonstrates in MC+HCV-p vs controls: (i) high serum CXCL9, and CXCL11, significantly associated with the presence of active vasculitis; (ii) a strong relationship between circulating CXCL9 and CXCL11. Future studies on a larger cohort of patients are needed to evaluate the relevance of serum CXCL9 and CXCL11 determination as clinico-prognostic marker of MC+HCV.